Case report: thermal helium in the treatment of coronavirus pneumonia caused by new coronavirus infection COVID-19 (SARS-CoV-2) - S. V. Zhuravel’; P. V. Gavrilov; N. K. Kuznetsova; I. I. Utkina; M. A. Talyzin; V. E. Aleksandrova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The novel SARS-CoV-2 coronavirus, which originated in December 2019 in Wuhan, China, has triggered an outbreak of a respiratory illness called COVID-19. Helium is a colorless inert gas, odorless and tasteless. Thermal helium-oxygen therapy is a new and innovative method that allows you to maintain the diffusion capacity of the lungs. The clinical case presented in this article shows that inhalation of a thermal gas mixture of helium and oxygen (t-He/O2) in the standard therapy of a patient with pneumonia caused by SARS-CoV-2 positively influenced the clinical picture of the disease, improves gas exchange, and promotes accelerating the elimination of the virus, rehabilitation and discharge of the patient.